Research on Stress Neutral Layer Offset in the Straightening Process. (8th December 2015) - Gui, Hailian; Li, Yao; Song, Hao; Huang, Qingxue
Abstract : The stress neutral layer offset is analyzed by theoretical and numerical calculation methods. In traditional straightening theory, the stress neutral layer was consistent with the geometric central layer. However, there is a phenomenon that the stress neutral layer has some offset with the geometric neutral layer. This offset is a very important factor for improving the precision of the straightening force. The formula of the stress neutral layer offset is obtained by a theoretical method and the change law is given by numerical calculation method. The neutral layer offset theory provides the theoretical basis for establishing the model of straightening force precisely.